Visual information reception effectiveness under different signal integrity - Gučas, A.; Penkauskas, A. (Psichologija, 1968)
This article discusses the layout integrity characteristics of the stimuli. It is concluded that there is insufficient stimuli layout integrity to consider only the most minimal distance, characterized by angular units between the nearest adjacent stimuli; rather, what we also need to enter the statistical average stimuli layout integrity characteristics that reflect the visual information signal parameters in relation to the visual field area. Visual information reception effectiveness examined the following conditions according to the above integrity characteristics: 1) The calculation of the unambiguous light signals chaotically set out in the field of vision, 2) searching for certain geometric figures when given an identification task, and 3) addressing a specific task in the mnemoschematic according to a pre-mastered algorithm. Based on experimental data, the optimal stimuli layout integrity characteristics are presented.